L’avventura nell’altrove: prassi d’orientamento e processi d’apprendimento in una società del cambiamento - La Rosa, Viviana (RESEARCH TRENDS IN HUMANITIES Education & Philosophy, 2014)
The article explores the crucial role played by the orientation/learning connection in an ever-changing society. The subject should be able to acquire awareness according to the instruments of knowledge, his own ways of reading the world, tastes, preferences, deepest and most intimate aspects that build his identity, so that he can explore new areas, the elsewhere, without being profoundly confused. The pedagogical task that derives from this principle is to build an educational proposal designed around the needs of the subject who knows, and focusing the growth path on his own cognitive styles, as well as on his experience. Donata Fabbri and Alberto Munari' s proposal of cultural psychology and operating epistemology and the Raffaele Laporta' s notion of learning are valuable in an attempt to translate this theoretical perspective into action. In response to this perspective, the student is called to be an aware interpreter of cognitive and ethical choices compared to what he studies, and to decline and negotiate continually the plan of his motivations depending on the context and encounters of life experiences. The subject, aware of the extraordinary story that lies behind every experience of knowing, and always in singular way, is placed in a position to express a willingness to learn, between motivation and choice (a dynamic described skilfully by Laporta). He seems to turn and refer to the notion of orientation naturally. In this way it seems possible to reintegrate the student in the function of "cultural maker", often betrayed by misguided training actions, as well as appreciate the discovery (even destabilising) of the new and unexpected, that is a propellant moment in view of the exploration of new forms of knowledge.